Study on biocharacteristics of Symbiodinium sp. isolated from soft coral in coastal water of Quang Nam, south central Vietnam - Hong, Dang Diem; Nhat, Pham Van; Huong Quynh, Hoang Thi; Tam, Luu Thi; Hoai Thu, Ngo Thi; Ha, Nguyen Cam; Lan Anh, Hoang Thi; Nam, Nguyen Hoai; Minh Hang, Nguyen Thi; Minh, Chau Van (Academia Journal of Biology, 2017)
Phototrophic dinoflagellates of the genus Symbiodinium (= zooxanthellae) are well known as symbionts of corals. They play an important role in maintaining the healthy as well as establishment of new reefs. In addition, products such as toxins or pigments from these symbiotic microalgae are potentially important for applications in the biomedical sciences, especially in new drug development. In this study, we isolated successfully a symbiotic microalga from soft coral Sinularia sp. which was collected in Cu Lao Cham coastal waters of Quang Nam province. Based on morphological characteristics and 18S rRNA gene sequences, isolated SHM8 strain was identified as Symbiodinium goreaui. This symbiont was cultured in different media such as ASP-A8, F2, ES, IMK, K, and L1. L1 culture medium supplemented with taurine concentration of 4.88 mM led to the cell density of SHM8 strain increased in 50% compared to control on day 2 in cultivation; amino acid mixture enhanced cell density by 31.7% on day 5 in cultivation. Supplementation of carbon source (bicarbonate salt of 16.8 g/L) and nitrogen source (nitrate salt of 0.055 g/L) enhanced the cell density by 40% and 27%, respectively on day 6 in culture. Obtained results in this study proved that this microalga can live independently without host. Successful isolation and cultivation of Symbiodinium microalga are one of the necessary conditions for promising researches on the natural bioactive substances from this microalgal biomass in the future in Vietnam. Citation: Dang Diem Hong, Pham Van Nhat, Hoang Thi Huong Quynh, Luu Thi Tam, Ngo Thi Hoai Thu, Nguyen Cam Ha, Hoang Thi Lan Anh, Nguyen Hoai Nam, Nguyen Thi Minh Hang, Chau Van Minh, 2017. Study on biocharacteristics of Symbiodinium sp. isolated from soft coral in coastal water of Quang Nam, south central Vietnam. Tap chi Sinh hoc, 39(3): 367-375. DOI: 10.15625/0866-7160/v39n3.10112. *Corresponding author: ddhong60vn@yahoo.com Received 19 June 2017, accepted 20 August 2017